How quality of service can affect an organization: A study on the importance of good customer service (Research, Society and Development, 2019)
This study's main objectives are present and understand the importance of customer service quality for institutions, linked to the current competitive environment, as a tool for survival, differential and business expansion. To better approach and understanding of the topic, the corpus of the research was based on an extensive literature search on the said topic, in order to add value and solidify knowledge here formulated. Based on these references, we will more assertively understand the impacts of an appropriate treatment of clients as a way not only of loyalty but also as a marketing tool for potential future clients through an informal but efficient advertising of funding, which is the indication.